Yevgeniya Mikhailovna Dumenova (tu the 100th anniversary) - A. I. Vengerovsky (Бюллетень сибирской медицины)
Scientific biography of Evgeniya Michaylovna Dumenova, famous Russian pharmacologist, chief of Pharmacology Chair in Tomsk Medical Institute is presented.